Current Strategies and Future Perspectives of Skin-on-a-Chip Platforms: Innovations, Technical Challenges and Commercial Outlook - ALARÇİN, EMİNE; YAŞAYAN, GÖKÇEN (BENTHAM SCIENCE PUBL LTD, 2018)
The skin is the largest and most exposed organ in the human body. Not only it is involved in numerous biological processes essential for life but also it represents a significant endpoint for the application of pharmaceuticals. The area of in vitro skin tissue engineering has been progressing extensively in recent years. Advanced in vitro human skin models strongly impact the discovery of new drugs thanks to the enhanced screening efficiency and reliability. Nowadays, animal models are largely employed at the preclinical stage of new pharmaceutical compounds development for both risk assessment evaluation and pharmacokinetic studies. On the other hand, animal models often insufficiently foresee the human reaction due to the variations in skin immunity and physiology. Skin-on-chips devices offer innovative and state-of-the-art platforms essential to overcome these limitations. In the present review, we focus on the contribution of skin-on-chip platforms in fundamental research and applied medical research. In addition, we also highlighted the technical and practical difficulties that must be overcome to enhance skin-on-chip platforms, e. g. embedding electrical measurements, for improved modeling of human diseases as well as of new drug discovery and development.
Keywords: Skin-on-chip; In vitro skin model; Skin tissue engineering; Microfluidic; Drug discovery and development; skin impedance; RECONSTRUCTED HUMAN EPIDERMIS; TRANSDERMAL DRUG-DELIVERY; MULTI-ORGAN-CHIP; IN-VITRO MODELS; HUMAN KERATINOCYTES; LANGERHANS CELLS; GROWTH-FACTOR; PERCUTANEOUS-ABSORPTION; MICROFLUIDIC PLATFORM; ENDOTHELIAL-CELLS